PENGARUH MODEL PEMBELAJARAN METAKOGNISI-SOCIAL COMPLEXITY TERHADAP KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Putri Pratama, Friska Aulia; Aqidatul Munfariqoh; Husna Imro’athush S (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school students' mathematical problem-solving skills are still low, particularly in understanding problems, determining strategies, and evaluating answers. Extensive research on metacognition has been conducted, but the integration of metacognition and social complexity based on collaborative interactions is still limited in elementary school mathematics learning. This study aims to analyze the effect of the social complexity metacognition learning model on students' mathematical problem-solving skills. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The study population consisted of 57 fifth-grade students of Kedungjenar State Elementary School in the 2025/2026 academic year, divided into experimental and control groups. Data were collected through pretests and posttests, then analyzed using the Mann-Whitney U Test. The results showed a significant difference between the two groups with a significance value of 0.000 (<0.05). The metacognition social complexity learning model helps students think more reflectively, systematically, and collaboratively when solving mathematical problems. This research contributes to the development of higher-order thinking skills-based mathematics learning in elementary schools.